Professionalization of Adult Education in Germany: Essential Scientific and Historical Discours - Гуляєва, Марія (LLC «Talkom», 2021)
The given article analyses the theories of professionalization, which conceptually define the essence and content of andragogy training in Germany. The research used general scientific (analysis, synthesis, generalization, systematization of collected material) and search and bibliographic methods (study of archival sources, legislation, historical, genetic and chronological analysis, which traced the understanding and formation of adult education evolution in Germany), as well as methods of definitive, theoretical and methodological, system-structural, structural and functional, and structural-logical analysis. It was found that the professionalism of the staff is a prerequisite for the functioning in social activity of any branch and sphere. It is proved that in Germany this issue has become especially relevant and is considered exclusively in the context of professionalization theories for a particular educational field. Theoretical principles and directions, models (mechanisms) and levels of professionalization are generalized, the essence of andragogy professionalism and professional habit of adult education specialist is specified. The main historical milestones in the understanding, interpretation and approval of the idea of adult education professionalization in Germany are highlighted. The scientific (theoretical and methodological, philosophical) and historical and practical (factual) approaches to the developed idea of professionalization in the outlined educational field are revealed. The existence and functioning at the qualitative level in the system of academic training for adult education specialists as a separate direction in the professionalization of the researched field is stated. Further research is necessary on the issues of antinomies and paradoxes observed within the actual field of adult education and its institutions, which is naturally reflected in the requirements for training, knowledge, skills and qualities of andragogy specialists.
Keywords: adult education; andragogue; vocational training; professionalism; professionalization of adult education in Germany